Analysis of Compensation and Job Satisfaction on Honorary Employee Performance at RSUD Pringadi Medan - Hutasuhut, Muhammad Anshari; Ahmadi Bi Rahmani, Nur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
One of the human resources who must have good performance is an honorary employee. In order to realize good employee performance, it is necessary to have supporting factors, namely compensation and job satisfaction. Compensation and job satisfaction will be received by honorary employees, which will encourage these employees to better comply with or obey the rules and norms that apply in the government system. So that compensation and job satisfaction are closely related to the realization of human resources that support employee performance. Unfair compensation can have an adverse effect or impact on employee performance, someone generally needs justice, especially workers or companies in an agency or company, where an employee expects appropriate rewards for the services or work, he has done. When the rewards or wages given are not suitable and cannot meet the needs of employees or employees, it will have an impact on their performance and will cause a problem in the company or agency which will ultimately harm the company or agency. The study aims to see how big the role of compensation and job satisfactionis is in supporting the performance of Honorary employees. This study uses the quantitative method with purposive sampling techniques and obtained sampling with the Slovin formula as many as 75 respondents will be distributed questionnaires to employees of Pringadi Hospital Medan. The results of this study indicate that there is a positive and significant influence between compensation and job satisfaction on the performance of honorary employees at Pringadi Hospital.